EFEK EKSTRAK DAUN CIPLUKAN (Physalis minima L) TERHADAP RELAKSASI OTOT POLOS TERPISAH TRAKEA MARMUT (Cavia porcellus) - Priyantoro, Sigit Tri Yus; Sudjari, Sudjari; Karyono, Setyawati S. (Fakultas Kedokteran Universitas Brawijaya, 2004)
Physalis minima L’s leaf contains atropin and skopolamin which possess anti cholinergic effect. Cholinergic agent has constriction effect to the smooth muscle of respiratory tract. In asthma bronchiale there is an airway constriction. This experiment was to observe the effect of Physalis minima L’s ethanol extract on the relaxation of the guinea pig’s trachea’s smooth muscle which was induced with histamin by the method of in vitro. Isolated trachea of 5 male guinea pig’s was used as samples in this experiment. Transducer, amplifier and mac lab computer were used to create the trachea’s contraction–relaxation curve. The independent variabel was Physalis minima L’s leaf ethanol extract dosage andthe dependent variabel was the trachea’s contraction. 4 dosage of Physalis minima L’s leaf ethanol extract were used (1 control, 3 comparable dosage), the dosage of 0.5 % Physalis minima L’s leaf extract showed significant relaxation of trachea (anova, p<0.05). There was a positive corelation between theincreasing dosage of Physalis minima L’s leaf ethanol extract and the relaxation of trachea (regression, r = 0.770, p< 0.05). The conclusion of this study is that the Physalis minima L’s leaf ethanol extract has positive effect in relaxing isolated trachea of guinea pig’s induced by histamin and there is a positive correlation between increasing dosageof Physalis minima L’s leaf ethanol extract and the relaxation of isolated trachea. Keywords:trachea smooth muscle’s relaxation, histamine, Physalis minima L’s leaf ethanol extract.